Response of garlic varieties growth towards the use of biological fertilizer - Dewi, Suryani; Zainuddin, Dian Utami; Angka, Andi Werawe (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
This study aimed to identify the response of local and imported garlic varieties' growth to biological fertilizer. The research was conducted in the Majene Regency, West Sulawesi, which began from April to July 2020. The research was arranged in a two-factor factorial Completely Randomized Design with 3 replications. The first factor is the variety of garlic which consists of two varieties, namely Sangga Sembalun and Kating. The second factor is the fertilizer that consists of three types, namely Trichoderma sp., Streptomyces sp., and Trichoderma sp. plus Streptomyces sp. The observations were made at the age of 7, 15, 30, and 45 DAS (Days After Sowing) where the parameters measured were the height of the plant (cm), the number of leaves (blade), the diameter of the bulb (cm) for each treatment. The observation data will be analyzed using the analysis of variance. The analysis of variance for the observation data used the F-test at a 5% significance level. Statistically, the findings of the research show that the treatments given are not significantly affected all parameters observed. The highest mean score on the treatment of biological fertilizers was the Trichoderma sp. plus Streptomyces sp. bacteria on both varieties tested. The results showed that in general, the biological fertilizer Trichoderma sp. plus Streptomycetes sp., gave better results, but it cannot be concluded that the imported Kating variety gave a better response than the local Sangga variety to all parameters, because the morphological or genetic characteristics of Kating and Sangga Sembalun may be also different.